Simulating the dynamics of T cell subsets throughout the lifetime - Foan, Stephanie; Jackson, Andrew M.; Spendlove, Ian; Aickelin, Uwe (Springer, 2011)
It is widely accepted that the immune system undergoes age-related changes correlating with increased disease in the elderly. T cell subsets have been implicated. The aim of this work is firstly to implement and validate a simulation of T regulatory cell (Treg) dynamics throughout the lifetime, based on a model by Baltcheva. We show that our initial simulation produces an inversion between precursor and mature Tregs at around 20 years of age, though the output differs significantly from the original laboratory dataset. Secondly, this report discusses development of the model to incorporate new data from a cross-sectional study of healthy blood donors addressing balance between Tregs and Th17 cells with novel markers for Treg. The potential for simulation to add insight into immune aging is discussed.